Risk Management Design For Light Vehicle Unit In Rental Company - Hanny Kanavika Rizky Munawar; Niniet Indah Arvitrida (Publikasi Indonesia, 2025)
This study aims to design risk management for a vehicle rental company in East Kalimantan using the Enterprise Risk Management (ERM) approach and the House of Risk (HOR) model. The transportation industry, particularly vehicle rentals, faces various risks that can disrupt the company's operations and performance. These risks include vehicle damage, delays in spare parts delivery, and payment issues from customers. This research will design Risk Management by applying Enterprise Risk Management (ERM) using the ISO 31000:2018 approach. In this study, the HOR method is used to identify, analyze, and prioritize risks and risk agents. This research combines the Failure Mode and Effect Analysis (FMEA) and Quality Function Deployment (QFD) methods to provide an integrated framework in risk management analysis. The results of the study indicate that the implementation of structured risk management can improve the company's operational effectiveness and efficiency. The proposed mitigation strategies include enhancing vehicle maintenance, staff training, and developing better monitoring systems. By implementing ERM and HOR, it is expected to manage risks more effectively, reduce the negative impact of occurring risks, and achieve the company's objectives more efficiently.